Pharmacokinetic comparison of sitagliptin and metformin HCl extended-release tablets versus JANUMET® XR in healthy volunteers under fasting and fed conditions - Que, Linling; Qin, Wei; Shi, Yunfei; Ding, Ying; Huang, Kai; Qian, Zhenzhong; Huang, Bingjie; Zhou, Peipei; He, Qing (Frontiers in Pharmacology, 2023)
Background and Objectives Janumet® XR is the combination of sitagliptin and extended metformin hydrochloride produced by Merck Sharp & Dohme. It is specially designed for diabetes mellitus patients taking both drugs already. Janumet® XR exhibited clinically significant blood glucose lowering efficacy and long-term use safety. However, no generic form of Janumet® XR has been approved in western countries. The relatively high cost made the medication less prescribed. A more affordable form of this drug may benefit an immense diabetes mellitus population. The current study compared the bioequivalence (BE) of sitagliptin 100 mg and metformin 1000 mg produced by Nanjing Chia-Tai Tianqing Pharmaceutical Company to Janumet® XR in healthy Chinese subjects. Methods Twenty-eight healthy Chinese subjects were enrolled in Study 1 and 2, respectively. Both studies were conducted with an open, randomized, two-period crossover design using the test (T) or the reference (R) drug. Study 1 is conducted under the fasting state, and Study 2 is under the fed state. Subjects received an oral dose of sitagliptin 100 mg and metformin 1000 mg, and plasma concentrations of sitagliptin and metformin were determined up to 72 h post-dose. Pharmacokinetic (PK) parameters, including maximum serum concentration (Cmax) and area under the concentration-time curve up to the last quantifiable concentration (AUC0–t) of both sitagliptin and metformin, were calculated and compared between the T and R treatments. Results In the fasting study, the geometric mean ratios of Cmax, AUC0–t, and AUC0-∞ for sitagliptin were 109.42%, 101.93%, and 101.95%, respectively; the corresponding ratios for metformin were 98.69%, 94.12%, and 93.42%, respectively. In the fed study, the geometric mean ratios of Cmax, AUC0–t, and AUC0-∞ for sitagliptin were 98.41%, 100.30%, and 100.24%, respectively; the corresponding ratios for metformin were 97.79%, 99.28%, and 100.69%, respectively. The 90% CIs of Cmax, AUC0–t, and AUC0-∞ in both studies were all within acceptance limits (80.00-125.00%). Conclusions The results demonstrated for the first time that sitagliptin 100 mg and metformin 1000 mg produced by Nanjing Chia-Tai Tianqing Pharmaceutical Company was bioequivalent to the branded Janumet® XR, and both drugs were well tolerated.